Efficiency of nitrogen acquisition and utilisation in common bean in Uganda - Wortmann, Charles S.; Silver-Rwakaikara, M; Lynch, J (1998)
Inadequate nitrogen nutrition is a major constraint to the performance of common bean (Phaseolus vulgaris L.) in sub-Saharan Africa. Twenty six lines selected for good performance under N-limiting conditions were further evaluated at two locations in Uganda to determine the mechanisms allowing good performance under soil N-limiting conditions. Two non-nodulating lines were included whose mean yield was 44% more with N application. The test lines showed little response to applied N implying that all fixed significant amounts of N2; N derived from the atmosphere was estimated to average 15 and 43% of plant N for two locations using the natural abundance 15N technique. Mean yield of test lines ranged from 810 to 1450 kg ha-1 across two locations with N-limiting conditions. Characteristics contributing to good performance under N-limiting conditions varied with genotypes which were grouped into two clusters, with four out-lying genotypes, based on N acquisition and utilisation characteristics. Nitrogen utilisation efficiency in vegetative growth was not important to yield under N-limiting conditions. Increased N acquisition during podfill was important to the yield of some genotypes, and presumably compensated for less biomass and plant N at the beginning of podfill. Yield was positively related to biomass and plant N at physiological maturity (R9), but not to N utilisation efficiency in biomass production at R9. Efficient partitioning of N from the vegetative parts to the grain was important to growth under N-limiting conditions, as was N utilisation efficiency in grain formation.